2002
DOI: 10.1016/s0893-133x(01)00293-7
|View full text |Cite
|
Sign up to set email alerts
|

Relapse to Cocaine- and Heroin-Seeking Behavior Mediated by Dopamine D2 Receptors Is Time-Dependent and Associated with Behavioral Sensitization

Abstract: The sensitizing properties of drugs of abuse have been proposed to play an important role in the persistence of drug seeking behavior. We decided to evaluate the temporal relationship of dopamine D2 receptor-mediated drug seeking behavior and behavioral sensitization in animals with a history of cocaine and heroin self-administration. During early phases of withdrawal ( Ͻ 1 week), activation of dopamine D2 receptors with quinpirole resulted in robust, dose-dependent, reinstatement of (non-reinforced) respondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
110
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 42 publications
13
110
2
Order By: Relevance
“…Given that prominent D 2 receptor sensitization develops in both low and high intake groups, and this overall effect was found in a previous study comparing cocaine to saline self-administration (De Vries et al, 2002), it is possible that D 2 receptor sensitization reflects intracellular alterations in D 2 receptor coupling, or an indirect enhancement via perturbations in neural input to D 2 -containing neurons, rather than an increase in D 2 receptor surface expression. Further investigation is needed to determine whether these changes are reflected in differential sensitivity to dopamine receptor-regulated biochemical or electrophysiological responses.…”
Section: Brain Cocaine Levelsmentioning
confidence: 70%
“…Given that prominent D 2 receptor sensitization develops in both low and high intake groups, and this overall effect was found in a previous study comparing cocaine to saline self-administration (De Vries et al, 2002), it is possible that D 2 receptor sensitization reflects intracellular alterations in D 2 receptor coupling, or an indirect enhancement via perturbations in neural input to D 2 -containing neurons, rather than an increase in D 2 receptor surface expression. Further investigation is needed to determine whether these changes are reflected in differential sensitivity to dopamine receptor-regulated biochemical or electrophysiological responses.…”
Section: Brain Cocaine Levelsmentioning
confidence: 70%
“…It is not clear, therefore, which of the many behavioral and psychological consequences of cocaine self-administration are due to changes in dorsal striatal D2 High receptors. Seeman and his colleagues (2002,2007) have reported that sensitization to amphetamine is associated with an increase in D2 High receptors, and both experimenter-administered cocaine and cocaine self-administration experience have been reported to produce behavioral supersensitivity to a challenge injection with a direct D2 receptor agonist (De Vries, et al, 2002, Edwards, et al, 2007. It has also been reported that both the limited and extended access cocaine self-administration procedures used in the current study produce psychomotor sensitization (Ferrario, et al, 2005, Knackstedt andKalivas, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, a long-standing puzzle in this area is that preclinical studies have consistently found that rats treated with amphetamine or cocaine, and then withdrawn, are hypersensitive to the psychomotor activating and incentive motivational effects of these "indirect agonists" (Robinson and Berridge, 1993), and even more importantly, to the psychomotor effects of direct-acting D2 agonists (Ujike, et al, 1990, De Vries, et al, 2002, Edwards, et al, 2007. Studies examining the effects of cocaine treatment on D2 receptor binding in rodents are mixed, with reports of increases (Trulson andUlissey, 1987, Peris, et al, 1990), decreases (Kleven, et al, 1990, Maggos, et al, 1998 or no change (Dwoskin, et al, 1988, Claye, et al, 1995.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cocaine priming significantly elevates extracellular NAc DA (Neisewander et al, 1996;McFarland et al, 2003;Xi et al, 2006). Also, systemic or intra-NAc administration of direct or indirect DA receptor agonists elicit, while DA receptor antagonists block, cocaine-induced reinstatement of drug-seeking behavior (Self et al, 1996;De Vries et al, 2002;Vorel et al, 2002). In addition, repeated cocaine administration produces enduring alterations in basal DA transmission, DA response to cocaine priming and/or expression of DA receptors in reward-related brain regions (Kuhar and Pilotte, 1996;Lu et al, 2003;Staley and Mash, 1996).…”
Section: Introductionmentioning
confidence: 99%